Exercise stress testing in healthy subjects during cholinergic stimulation after a single dose of pyridostigmine - Serra,Salvador M. (2001)
OBJETIVE: The evaluation, by exercise stress testing, of the cardiorespiratory effects of pyridostigmine (PYR), a reversible acetylcholinesterase inhibitor. METHODS: A double-blind, randomized, cross-over, placebo-controlled comparison of hemodynamic and ventilation variables of 10 healthy subjects who underwent three exercise stress tests (the first for adaptation and determination of tolerance to exercise, the other two after administration of placebo or 45mg of PYR). RESULTS: Heart rate at rest was: 68±3 vs 68±3bpm before and after placebo, respectively (P=0.38); 70±2 vs 59±2bpm, before and after pyridostigmine, respectively (P<0.01). During exercise, relative to placebo: a significantly lower heart rate after PYR at, respectively, 20% (P=0.02), 40% (P=0.03), 80% (P=0.05) and 100% (P=0.02) of peak effort was observed. No significant differences were observed in arterial blood pressure, oxygen consumption at submaximal and maximal effort, exercise duration, respiratory ratio, CO2 production, ventilation threshold, minute ventilation, and oxygen pulse. CONCLUSION: Pyridostigmine, at a dose of 45mg, decreases heart rate at rest and during exercise, with minimal side effects and without interfering with exercise tolerance and ventilation variables.